The effect of mitomycin-c in keloid fibroblast cultures - Ishandono Dachlan; Teguh Aryandono; Mae Sri Hartati Wahyuningsih; Hardyanto Soebono; Yohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTKeloid occurs due to hyperactivity of keloid fibroblast (KF) in proliferation, migration, collagen deposition, together with low rates of collagen degradation. These are under the responsibility of TGF-b. Mitomycin C (MC) is used for treating keloid by a topical application during surgery at the level of 0.02% to 0.08%. Unfortunately, the lowest effective level of MC for keloid has not been determined yet. We aimed to determine the lowest effective level of MC in the suppression of KF activities. Various levels of MC diluted in growth medium were administered on KF that were isolated from six patients. After 24 hours and 72 hours of incubation, cellular proliferation, collagen deposition, cellular migration and level of TGF-b, were analyzed. Application of 120 uM MC on KF culture for 24 hours could significantly reduce TGF-b production from 1265.74 ± 274.81 pg/mL to 265.17 ± 12.20 pg/mL; proliferation index from 100% to 84.01 ± 12.91%; inhibit cellular migration to 64.38 ± 3.66%; but reduce collagen depositions from 100% to only 91.13 ± 10.19%. The lowest MC level is on 30 uM or equal with 0.001%. In conclusion, the lowest level of MC can suppress the activities of KF is 0.001%. Moreover, due to low activity in inhibiting collagen deposition, MC would be better as an adjuvant drug for keloid surgery.